Rekonstruksi Model Murid Mubadir (Inisiator): Analisis Pedagogis Kisah Sulaiman dan Hud-hud (QS. An-Naml: 20-28) - Ahmad Dimyati Ridwan; Cucu Surahman; Elan Sumarna; Zakia Fitri Nabila; Intan Wardatul Karimah (Fakultas Agama Islam, 2026)
Studies on the concept of the disciple in the Qur'an are often dominated by the